Port Interconnectivity through the Prism of African Pottery and Amphorae - (:unkn) unknown (My University, 2019)
Even if the ability of ceramics to reconstruct trade flows and direction may have been over-emphasized during these last decades, pottery and amphorae produced in Africa from the 2nd to the 7th century, due to their ubiquitous presence throughout the Mediterranean, still remain one source among others to our understanding of Roman port interconnectivity. After recalling the progress made in improving traceability of these wares, this paper will first focus on Sicily, where the survey recently carried out with Daniele Malfitana in the footsteps of Lisa Fentress, permitted to define three different patterns of port interconnectivity capable to explain the differences in the supply of African ware in the island. Then, comparisons will be search in other places of the Mediterranean over time, in order to verify the capacity of African pottery to provide information on the commercial routes between African key ports and the City or the rest of the ‘Roman’ world. Lastly, a first attempt to periodisation from the Republican period to late Antiquity will be proposed, seeking to identify the different turning points of these networks.
Keywords: African Research